MEKANISME PEMILIHAN MPR DENGAN CONGESTION DETECTION DALAM OLSR PADA MANET - Hartawan, I Nyoman Buda; Wibisono, Waskitho (Jurnal Ilmu Komputer, 2013)
MANET (Mobile Ad-hoc Network) is a collection of mobile nodes which comunicate each others usingwireless network. MANET does not have fixed network infrastructure. OLSR (Optimized Link State Routing) is arouting protocol in MANET. In OLSR there is a selection of neighbor nodes as MPR (Multi Point Relay) forforwading packet data from source to destination. MANET characteristics which shared medium to comunicatewirelessly, causing congestion vulnerable occurs in intermediate node when packet data transmission fromsource to destination. The congestion that occurs in network can lead to high packet loss and long delay, thuscausing reduction of network performance. This study aims to perform the selection of MPR in OLSR withcongestion detection methods in MANET. Results of the study showed that MPR selection with congestiondetection in OLSR can improve packet delivery ratio and network throughput when packet transmission fromsource to destination. This study simulated on Network Simulator version 2 (NS-2).
Keywords: MANET; OLSR; Multi-Point Relay; congestion detection; NS-2